An investigation into buddhism meditation works and their vietnamese translated versions - Nguyễn,Hồ Ngọc Anh Tuấn (ĐHNN, 2016)
This thesis investigated the most common types of Strategies for Translating Religion-specific terminologies used in the translation of Vietnamese words. This aims at assisting learners of English in classifying meanings of English meditation terminologies as well as their equivalents in Vietnamese in order to use them appropriately in especially translation. We are interested in dealing with the loss of meaning in the translation of Buddhism meditation works from English to Vietnamese versions in Buddhist documents. We normally have difficulties in understanding Buddhist terminologies in English. So doing research on the strategies and procedures that may apply to the translation of Vietnamese, cultural words must be useful for our students and us to improve their skills of reading English Buddhism documents. The researcher used a contrastive analysis to complete this study. The researcher took this method from the statement by (Goetz, J. P., and LeCompte, M. D., 1985, p. 87). The data extracted from the book “Three pillars of Zen” and the Vietnamese versions entitled “Ba trụ thiền”. There are 300 utterances in each version of the Buddhism meditation work, English and Vietnamese version to find out the phenomena of loss and gain take place regularly in the translational version the book” Three pillars of Zen” in the present thesis. We can see that it is very difficult to translate religious texts. Finding out the loss of meaning in the translation of Buddhism meditation works from English to Vietnamese versions has been concerned as well. This is for helping readers of English apply in language skills as well as translation of English religious contexts into Vietnamese and vice versa
Keywords: buddhism meditation works